Biomineralization Potential of Bacillus subtilis, Rummeliibacillus Stabekisii and Staphylococcus Epidermidis Strains In Vitro Isolated from Speleothems, Khasi Hill Caves, Meghalaya, India. Issue 8 (14th September 2018) - Mudgil, Devender; Baskar, Sushmitha; Baskar, Ramanathan; Paul, D.; Shouche, Yogesh S.
ABSTRACT: Microorganisms were isolated and identified from speleothems at Khasi hill caves, Meghalaya. The aim was to understand their biomineralization potential. Analyses of the speleothems from Krem Soitan, Krem Mawpun, and Krem Lawbah using scanning electron microscope (SEM) showed evidences for microbe–mineral interactions. SEM showed microbial reticulate and beaded filaments, cells, fiber calcites, and clusters of coccoid-like structures. A total of 113 bacterial strains were isolated and identified by a combination of conventional and molecular based tools. 105 strains that were sequenced belonged to the genus: Bacillus, Rummeliibacillus, Staphylococcus, and Brevibacterium . The BLASTn sequence search of 16S rRNA sequences with the National Centre for Biotechnology Information database to establish the identity of the strains yielded similarity scores of ≥99% with the respective organisms. The strains were identified as Bacillus simplex, Bacillus gaemokensis, Bacillus subtilis, Bacillus thuringiensis, Bacillus albus, Bacillus cereus, Bacillus anthracis, Bacillus weihenstephanensis, Rummeliibacillus stabekisii, Bacillus wiedmannii, Staphylococcus epidermidis, Rummeliibacillus pycnus, Kurthia zopfii, and Brevibacterium frigoritolerans . These strains were tested for biomineralization on B-4 medium. Five strains ( B. subtilis, R. stabekisii, Staphylococcus epiderdimis, B. cereus, and B. wiedmannii ) had the capability to precipitate biominerals in vitro. B. subtilis, R. stabekisii, and S. epidermidis precipitated 0.24, 0.36, and 0.35 g/L of biominerals at 22°C at the end of the four week experiment period. These strains increased the pH of the medium from 7 to 8.95. The precipitated biominerals were imaged using an ultra-high resolution field emission SEM. X-ray diffraction of the biomineral precipitated by R. stabekisii showed that it was composed of vaterite and jungite. Whereas S. epidermidis showed that it was composed of calcite, vaterite, and jungite. B. subtilis produced small, circular calcite crystals. This is the first comprehensive report on the possible evidences about the role of R. stabekisii and S. epidermidis in calcite precipitation isolated from speleothems in the Indian caves. These results allow us to postulate that the identified strains have biomineralization potential. Further evidences of the coexistence of exopolysaccharides, whisker fiber calcites, microbial filaments, and coccoid-like forms point to biogenic inputs in the cave mineral formations.